Drug-induced fulminant hepatic failure in pregnancy. (December 2015) - Firoz, Tabassum; Webber, Douglas; Rowe, Hilary
Liver disease in pregnancy can be classified as predating, co-incidental or unique to pregnancy. Medications are often overlooked as a significant cause of liver disease. We present the case of a 39-year-old patient who presented at 20 weeks with jaundice, elevated liver enzymes, and abnormal liver function progressing eventually to fulminant hepatic failure. The patient was on methyldopa and labetalol from 12 weeks' gestational age. Liver biopsy was consistent with drug-induced liver injury. Both methyldopa and labetalol have been associated with hepatotoxicity including liver failure. This case highlights the importance of including medications as a cause of liver failure in pregnant patients.